Vowels in Malacca Portuguese Creole - Pillai, Stefanie; Chan, Min En; Baxter, Alan Norman (Research in Language, 2015)
This paper examines the vowel system of present day Malacca Portuguese Creole (MPC) or Kristang, based on recordings from interviews with five female native speakers of MPC. A total of 1083 monophthongs were extracted from the recordings. The first and second formants of these vowels were measured and analysed. Considerable variation was found within and between the speakers in the way each of the vowels was produced. There were also noticeable overlaps between /i/ and /e/ suggesting that they were being used interchangeably. Based on the variation in the way that vowels are produced, and the overlaps between vowels, the findings suggest the possibility of phonological instability of this endangered language.